2022
DOI: 10.1021/acsomega.2c06174
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Assisted Prediction of the Biological Activity of Aromatase Inhibitors and Data Mining to Explore Similar Compounds

Abstract: Designing molecules for drugs has been a hot topic for many decades. However, it is hard and expensive to find a new molecule. Thus, the cost of the final drug is also increased. Machine learning can provide the fastest way to predict the biological activity of druglike molecules. In the present work, machine learning models are trained for the prediction of the biological activity of aromatase inhibitors. Data was collected from the literature. Molecular descriptors are calculated to be used as independent fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…13–15 Machine learning has the ability to predict almost every property for which enough data are available. 16–18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13–15 Machine learning has the ability to predict almost every property for which enough data are available. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Machine learning has the ability to predict almost every property for which enough data are available. [16][17][18] Sanchez-Lengeling et al reported a machine learning approach based on the Bayesian method to predict Hansen solubility parameters. Various types of inputs such as SMILES strings, COSMOtherm simulations, and quantum chemistry calculated properties were used as inputs.…”
Section: Introductionmentioning
confidence: 99%
“…ML employs algorithms for data visualization and analysis, and it has numerous advantages over traditional programming methods. ML has proven useful in a variety of fields, including transcription and image identification 34 …”
Section: Introductionmentioning
confidence: 99%
“…ML has proven useful in a variety of fields, including transcription and image identification. 34 In the present study, to design new building block units, benzofuran-based blocks are used as a standard. Benzo[1,2-b:4,5-b 0 ]dithiophene (BDT) has been extensively used to design polymers for photovoltaics applications; however, benzo[1,2-b:4,5-b 0 ]difuran (BDF) has rarely been utilized in photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The data science technology known as machine learning (ML) employs new methods and formulas to solve complicated issues that are challenging to write using conventional programming techniques [24][25][26][27]. The ML analysis is based on collecting sufficient trustworthy material data (either experimental or computational) that best describes the behavior or quality of the material or its applications to create models for finding new materials without having to repeat the same experiments or calculations [28,29].…”
Section: Introductionmentioning
confidence: 99%